Field investigation of steel pipe pile under lateral loading in extensively soft soil - Yi, Shixuan; Liu, Jianmei; Gu, Meixiang (Frontiers in Materials, 2022)
The construction of railway and highway embankments has a significant influence on the behavior of existing pile foundations, especially in the situation of the high embankment and extensively soft soils, which was commonly encountered in the coastal area. The high embankment might produce large lateral movement and bending moment to the existing adjacent piles, which would cause the failure of the pile if the surcharge loading was not properly considered. A field test was designed and performed to investigate the effect of lateral surcharge loading on the existing adjacent pile in extensively soft soils. A 4 m high embankment was constructed in 5 lifts and was close to the existing adjacent steel pipe pile with a length of 35 m. The deformation of the pile and the soft soils, the excess pore water pressure, and lateral earth pressures were measured during the surcharge loading test. The test results show that the lateral displacement of the steel pipe pile at the ground surface exceeded 229.9 mm and cannot maintain constant due to the surcharge loading. The lateral displacement decreased along with the pile depth and was relatively small when the pile depth exceeded 10 m. Large lateral displacements were observed in the soft soils at different locations. The surcharge loading zone showed obvious downward displacements, while the soft soils close to the loading zone showed upward displacements. The excess pore water pressure changed regularly with the construction of the embankment, and its maximum value reached 53.6 kPa. The lateral earth pressures acted on the pile continuously increased with the increase of the embankment height, which caused large deformation of the pile.